2014
DOI: 10.1080/08897077.2013.792760
|View full text |Cite
|
Sign up to set email alerts
|

Harm Reduction Behaviors among Young Polysubstance Users at Raves

Abstract: This study provides empirical information that may be useful for harm reduction intervention in a hidden and hard-to-reach population like rave attendees. The results point to the need to inform and increase harm reduction behavior specifically aimed at polysubstance use by ravers, especially among more frequent users. Future directions for research are also suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
4
18
0
3
Order By: Relevance
“…Previous research has found that memory impairments are regularly reported among polysubstance users , as is the case in our study. Our results highlight the importance of frequent adoption of two dosing‐related harm reduction strategies to minimise this harm.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Previous research has found that memory impairments are regularly reported among polysubstance users , as is the case in our study. Our results highlight the importance of frequent adoption of two dosing‐related harm reduction strategies to minimise this harm.…”
Section: Discussionsupporting
confidence: 85%
“…Some of the harm reduction strategies identified in this study have also been identified in previous research; for example, regulating the quantity of drugs used, spacing out doses within a session of substance use, and not combining multiple stimulants or depressants . Participants reported high prevalence of use of dosing‐related harm reduction strategies.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations